The panorama of corporate environmental sustainability and green values: evidence of Bangladesh - Hossain, Mohammad Imtiaz; Ong, Tze San; Tabash, Mosab I.; Teh, Boon Heng (Springer Dordrecht, 2024)
Corporate environmental sustainability is gradually becoming consciously recognised by textiles due to increasing pressure from diverse stakeholders and enhancing competitiveness. However, the textiles in developing countries continue to face issues such as severe water pollution, emissions, and increased carbon footprint, despite using various recycling techniques. To tackle these ecological issues, micro- and macro-factors must be incorporated into sustainable policies and practices. Considering this, the current empirical study aims to assess the influence of employees' green behaviour (EGB) and organisational green culture (OGC) on environmental sustainability practices (ESP) among textile small and medium enterprises (SMEs) in Bangladesh. Furthermore, based on these relationships, the study examined the moderating role of green technology adoption (GTA). A conceptual model has been proposed. The quantitative methodology was employed with a self-administrated structured questionnaire, followed by a cross-sectional research design to test the model. The data were collected from employees of 140 textile SMEs in Dhaka and analysed using the structural equation modelling (SEM) technique (SmartPLS 3 software). The results revealed the primary outcome, a significant relationship between EGB and OGC with ESP. GTA played the moderating role between EGB and ESP. The study's novelty contributes to the existing literature on sustainability in an organisational setting by assessing these relationships and testing the moderation effects. Theoretically, this study contributes by applying the theory of planned behaviour and Self-determination theory to explain the constructs. Besides contributing to the literature and theories, the study also offers many empirical insights for the industry, regulatory bodies, and other stakeholders of developing countries, especially Bangladesh. The study outcomes guide the decision-makers to formulate green strategies and encourage the employees' green behaviour and commitment to the organisations in the wake of greening the textile manufacturing sector. The study also identifies the need to incorporate GTA and OGC into textile SMEs to encourage positive EGB and increase ESP.